Oral Manifestations of Patients Diagnosed with Dermatological Diseases: A Cross-Sectional Study in Eastern Province, KSA - Venkata Subramanyam Ramadugula, Syed Akhtar Hussain Bokhari, Hazem Tarek Rashed, Rakan Rafdan Alhujhuj, Essa Yousef Al-Abdullredha, Hesham Hamad Al-Shuaibi (Pakistan Journal of Medical & Health Sciences, 2022)
Background: It is not unusual for oral manifestations to occur in dermatological diseases. The aim of this study was to observe and evaluate oral manifestations in patients diagnosed with dermatological diseases. Methods: A cross-sectional study based on a convenient sampling technique was conducted among patients with dermatological conditions who visited the polyclinic of King Faisal University Polyclinic of Al-Ahsa, Saudi Arabia from Sep-Nov 2021. Results: Sixty-one percent were females, 50% were aged >30 years, 77% had higher education, 61% were unemployed, 82% were non-smokers, and 20% had some medical conditions. 14.5% suffered from immune-mediated skin disease, 25.3% had eczema, 21.7% showed dermatitis infections, 3.6% had Genodermatosis, 9.6% were with psoriasis and other keratinizing disorders, and 25.3% had miscellaneous skin conditions. 85.5% of skin patients did not have any oral manifestations; oral lesions were of perioral dermatitis (1.2%), melanotic macule (1.2%), fissured tongue (2.4%), oral lichen planus (2.4%), mucocele (2.4%), and one case of each with geographic tongue, herpes labialis, and hairy tongue. Practical ImplicationsThis study highlights the importance of integration of oral health into general health for management of oral diseases associated with other body diseases. Conclusion: The majority of the patients in this study sample with skin diseases did not show any oral manifestations. More females and aged patients had more skin conditions. Keywords: Prevalence, Oral manifestations, Dermatological conditions, Cross-sectional study